Manajemen Mutu Pendidikan Adaptif di Era Disrupsi: Integrasi Kepemimpinan Digital dan Sistem Penjaminan Mutu Berkelanjutan - Apri Pil Bahrul Ulum; Afen Khaer Afendi; Susiyanti Susiyanti; Bayu Irawan; Fauzi Fauzi (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the synergy between education quality management and transformational leadership as a strategy in increasing the effectiveness and competitiveness of educational institutions in the era of globalization and digitalization. The approach used is a literature study by examining relevant theories from various academic sources, both national and international, which discusses the basic concepts of quality management, the characteristics of transformational leadership, and the implementation of both in the context of education. The results of the study show that quality management functions as a management system that ensures the sustainability of improving the quality of education through the principles of planning, implementation, evaluation, and continuous improvement. Meanwhile, transformational leadership acts as a driving force that provides inspiration, motivation, and moral direction to all members of educational organizations. The synergy between the two forms a managerial pattern that is not only systemically efficient, but also humanist and visionary in value. Transformational leaders are able to internalize a culture of quality into every educational process, so that quality is no longer understood as an administrative obligation, but as a collective commitment to produce graduates with excellence and character. This study confirms that the integration of quality management and transformational leadership is the main foundation for the creation of adaptive, innovative, and sustainable educational institutions in the midst of the challenges of the 21st century.